First European quality of life survey key findings from a policy perspective - Daly, Mary.; Rose, Richard; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
A favourable quality of life is integral to the European social model. Europe has long promised its citizens greater access to a broad range of life opportunities and that public resources will be channelled to enable people to realise their preferences and expectations. At the same time, Europe relies heavily on collective institutions and shared values. Among the fundamental features of European society are a high degree of integration between economic and social policy, the presence of a well-developed architecture of public social provision and the anchoring
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books